A relação dos estilos de gerenciar líderes na motivação dos colaboradores: um estudo na ACM - RS - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This study investigates the relationship between styles of managing the leaders in motivating employees. Therefore, we carried out a descriptive study with a quantitative and with the research strategy the survey approach. The study was applied to the Young Men's Christian Association of Rio Grande do Sul (YMCA-RS), and a sample of 84 employees from different units in the State. The research application of instruments used were questionnaires Manage Style Assessment Scale (MSAS) built by Melo (2004) and the Motivation Scale (Multi-Moti), built by Ferreira et al., (2006). Data were analyzed using descriptive statistics, Cronbach's alpha and Spearman correlation. Regarding the style of managing adopted by the leaders of the organization, the results show that they are more focused on the relationship factor. In relation to the motivational factors, the motivation factor for the performance achieved a higher average, showing that the organization's employees are motivated by the goals. The correlation between the managing and motivational style factors indicate that the factors Relations and Motivation with Labour Organization (0.415) show a moderate association index, the only correlation between style of managing and motivating factors. So, as the main result of this study it is clear that the more the leader uses the Relationship style, most employees feel motivated towards the organization of work.
The relationship between leadership management styles and employee motivation: a study at ACM - RS
Keywords: Liderança; Motivação; Papel do líder; Leadership; Motivation; Leader's role; CNPQ::CIENCIAS SOCIAIS APLICADAS